Prioritization of climate induced gender specific vulnerability issues in crop and dairy enterprises - CHAKRAVARTY, RITU; PONNUSAMY, KUPPUSAMY; SENDHIL, R (The Indian Journal of Animal Sciences, 2021)
The study identified and prioritized the climate induced gender specific vulnerability of the selected households pursuing crop and dairy enterprises in the three villages, one each from Karnal, Yamunanagar and Sirsa districts of Haryana, adopted under the Technology Demonstration Component of the National Innovations in Climate Resilient Agriculture (NICRA) Project. As per the Intergovernmental Panel on Climate Change, data were collected from 90 households (30 households / village) and then computed the overall vulnerability index based on the exposure, sensitivity and adaptive capacity indices, using 17 indicators extracted through Principal Component Analysis. High vulnerability was found in 21.11% households (mean vulnerability index value of 0.6201) and 41.11% households were found vulnerable to a medium level (mean vulnerability index value 0.3631). Significant difference was revealed in the overall exposure and overall adaptive capacity between districts. The overall vulnerability was found highest in Yamunanagar (0.3846), followed by Sirsa (0.3671) and Karnal (0.3043) districts. The identified gender prioritization of vulnerability issues needs to be addressed in each district as well as on aggregate basis for increasing resilience and decreasing gendered household vulnerability.